2015
DOI: 10.1038/jhg.2015.130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical and mutation profile in Indian patients with Sandhoff disease

Abstract: Sandhoff disease (SD) is an autosomal recessive neurodegenerative lysosomal storage disorder caused by mutations in HEXB gene. Molecular pathology is unknown in Indian patients with SD. The present study is aimed to determine mutations spectrum and molecular pathology leading to SD in 22 unrelated patients confirmed by the deficiency of β-hexosaminidase-A and total-hexosaminidase in leukocytes. To date, nearly 86 mutations of HEXB have been described, including five large deletions. Over all we have identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…Pattern of generalized tonic-clonic seizures and myoclonic seizures exacerbated by loud noise was consistent with previous observation [3]. Unlike TSD, mild hepatosplenomegaly can be noted in SD as also found in one patient of the present cohort (patient-3) [24]. Cardiac involvement including cardiomegaly, valvulopathies, hypertrophic/dilated cardiomyopathy is an uncommon finding, it is rare but could be a presenting feature of infantile SD and even ahead of neurological manifestation [25,26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pattern of generalized tonic-clonic seizures and myoclonic seizures exacerbated by loud noise was consistent with previous observation [3]. Unlike TSD, mild hepatosplenomegaly can be noted in SD as also found in one patient of the present cohort (patient-3) [24]. Cardiac involvement including cardiomegaly, valvulopathies, hypertrophic/dilated cardiomyopathy is an uncommon finding, it is rare but could be a presenting feature of infantile SD and even ahead of neurological manifestation [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…HEXB gene is the only gene known to cause SD with approximately 107 variants described with the vast majority being missense and nonsense variants [29]. Most of the HEXB pathologic variants are family-specific but common HEXB variant have been observed in certain ethnic groups such as c.850C>T (p.Arg284*) in Indian population [24], c.171delG (p.Trp57CysfsX6) in Spanish descendants [30], and c.115delG (p.Val39fs) in northern Saskatchewan population of Canada [27]. Possible genotype-phenotype correlation has been suggested, for example c.626C>T (p.Thr209Ile) and c.1404delT (p.P468PfsX62) are likely linked to the infantile form of SD [31].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in charge and size could possibly have some detrimental effects on external interactions and interactions with internal molecules. The same mutation was previously reported in many countries in patients with Sandoff disease (13,(46)(47)(48). Zampieri et al(2012) found that the activity of the affected protein is considerably diminished or completely absent compared to the normal protein, and they predicted the mutant residue C533 could form a disulphide bond with C551 which normally forms this bond with C534, and that could result in severe misfolding of the C terminal loop of the protein (49).…”
Section: Disscutionsupporting
confidence: 61%
“…Cherry-red spots on fluoroscopy examination and hyperacusis are the essential clinical clues to diagnosing SD. 2,9 Here, cherry-red spots in all eight cases helped early suspicion of iSD, but hyperacusis was present only in three cases.…”
Section: Discussionmentioning
confidence: 91%